A survey of capital budgeting techniques used by australian firms - Pratheepkanth, P.; Premkanth, P. (University of Jaffna, 2018)
Capital budgeting (CB) encompasses making investment decisions concerning the financing of investments by firms. This research examines the CB techniques employed by Australian firms to ascertain whether CB techniques vary significantly among the firms and whether these variances can be explained by differences attributed to different firms and its CFOs attributes. This study adopts a quantitative approach. There was a structured questionnaire survey to discover the CB techniques in the context of Australia, as an example of a developed market. The questionnaires were posted to 150 Australian firms, asking about the firm and the respondent’s demographics along with various aspects of CB techniques, giving a response rate of 48.7 percent. The results revealed that Australian firms tend to use sophisticated techniques (i.e. NPV, IRR, WACC and CAPM) as their most frequently used CB techniques and the usage appears to be more common and important than what hasbeen noted in many earlier studies. However, PBP is also prevalent (83 percent). This indicates that the sophistication of CB techniques appears to be significantly (if not mostly) influenced by attributes of the firm and the respondents. This finding supports the contingency theory—i.e. the CB techniques/investment approach of a firm should fit with the firm’s attributes and those of its principles.
Keywords: Capital budgeting; Sophisticated techniques; Investment approach